Corrections to: Experimental and Numerical Demonstration on the Gain and Power Saturation of Yb-Doped Double-Clad Fiber Amplifiers in Multiwavelength CW and Ultrafast Pulsed Operation - Mohamed A. Abdelalim; Hussein E. Kotb; Ebin Joseph; Ahmed M. Othman; Hanan Anis (IEEE Photonics Journal)
Presents corrections to the above named paper.